Critical Ecologies : The Frankfurt School and Contemporary Environmental Crises - Biro, Andrew, 1969- (Book collections on Project MUSE., 2011)
Critical Ecologies argues that sustainability and critical social theory have many similar goals, including resistance to different forms of domination. Like the Frankfurt School itself, the essays in this volume reflect a spirit of interdisciplinarity and draw attention to intersections between environmental, socio-political, and philosophical issues. Offering textual analyses by leading scholars in both critical theory and environmental politics, Critical Ecologies underscores the continued relevance of the Frankfurt School's ideas for addressing contemporary issues."--Publisher description.